Statistics and data analysis an introduction - Siegel, Andrew F. (John Wiley, 1996)
Combining the traditional foundations of statistical methods with the more modern ideas of data analysis, this text includes a range of problems that are both straightforward and challenging. The solution to each problem is described in a gradual progression of logical steps.